Interpersonal Communication, Transformational Leadership, and Workload on Employees’ Performance at PT Sawit Riau Makmur - Andi; Puteri, Cinderella; Kudri, Wan Muhamad (Luxury: Landscape of Business Administration, 2023)
The purpose of this research is to analyze the effect of interpersonal communication, transformational leadership, and workload on employee performance. This research was conducted at PT Sawit Riau Makmur Rokan Hilir. The population in this study were all employees of PT Sawit Riau Makmur Rokan Hilir, totaling 76 people. Due to the relatively small population size, the entire population was sampled in this study using the census method. The results of this study explain that communication has no significant effect on employee performance, leadership has no significant effect on employee performance, and workload has a positive and significant effect on employee performance at PT Sawit Riau Makmur Rokan Hilir.